Computational Thinking (CT) Problem Solving Orientation Based on Logic-Decomposition-Abstraction (LDA) by Rural Elementary School Children Using Visual-Based Presentations - Zaman, Halimah Badioze; Ahmad, Azlina; Nordin, Aliimran; Yamat Ahmad, Hamidah; Aliza, A.; Ang, M. C.; Shaiza, N. Azwan; Riza, S.; Normazidah, C. M.; Azizah, J.; Wahiza, W.; Nazlena, M. A.; et al. (Advances in Visual Informatics, 2019)
This qualitative and ethnographic study examines how interactions embedded in the Collaborative Computational Thinking Design Practices (CCTDP) framework, has helped rural children think to solve STEM related open ended problems in English lessons. Our multimodal interactive approach revealed that students naturally has an orientation to problem solving that can be nurtured and trained towards a certain preferred computational thinking concept practices. The CCTDP has specifically three problem solving orientations, but this paper highlights only one of these orientation; ‘logic-decomposition-abstraction’ (LDA) orientation which is identified as the second level of problem solving orientation in the CCTDP framework. This study also highlights the importance of group interactions in computational design thinking practices integrated in learning of English across science, technology, engineering and mathematics (STEM).